2018
DOI: 10.1080/10408398.2017.1423276
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression and vitamin D: A systematic review

Abstract: Postpartum depression (PPD) is a prevalent mood disorder estimated to affect 20%-40% of women worldwide after childbirth. In recent studies, the effect of vitamin D on prevention of mood disorders and depression has been investigated, but it is still unclear how vitamin D may affect PPD. The evidence on the relevance between vitamin D deficiency and PPD is inconsistent, and assessment of the recent literature has not previously been carried out. Moreover, there are few clinical studies on PPD and vitamin D sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 47 publications
0
41
0
1
Order By: Relevance
“…Importantly, meta-analyses of observational studies documented that low serum 25(OH)D concentrations in pregnancy are associated with increased risk of small for gestational age (SGA) and preterm birth [ 90 , 91 , 92 ]. Some meta-analyses have also shown that vitamin D deficiency is associated with postpartum depression [ 93 , 94 , 95 , 96 ]. Other outcomes such as fetal bone growth or neonatal lung maturation may also be associated with vitamin D status, but more data are needed on these topics [ 97 , 98 ].…”
Section: Pregnancy Outcomesmentioning
confidence: 99%
“…Importantly, meta-analyses of observational studies documented that low serum 25(OH)D concentrations in pregnancy are associated with increased risk of small for gestational age (SGA) and preterm birth [ 90 , 91 , 92 ]. Some meta-analyses have also shown that vitamin D deficiency is associated with postpartum depression [ 93 , 94 , 95 , 96 ]. Other outcomes such as fetal bone growth or neonatal lung maturation may also be associated with vitamin D status, but more data are needed on these topics [ 97 , 98 ].…”
Section: Pregnancy Outcomesmentioning
confidence: 99%
“…There have been many studies exploring the potential associations between vitamin D and psychological phenomena or psychiatric disorders, including depression (Alavi, Khademalhoseini, Vakili, & Assarian, 2018; Amini, Jafarirad, & Amani, 2018; Bertone‐Johnson et al, 2012; Dumville et al, 2006; Ghaderi et al, 2017; Jorde, Sneve, Figenschau, Svartberg, & Waterloo, 2008; Khoraminya, Tehrani‐Doost, Jazayeri, Hosseini, & Djazayery, 2013; Pittampalli et al, 2018), anxiety (Armstrong et al, 2007; Huang et al, 2014; Pu et al, 2018), psychotic disorders (Chiang, Natarajan, & Fan, 2016), cognitive impairment (Degner, 2016; Etgen, Sander, Bickel, Sander, & Forstl, 2012), sleep disturbance (Gao et al, 2018; Ghaderi et al, 2017), autism spectrum disorder (Moradi et al, 2018; Patrick & Ames, 2014), and substance use (Ghaderi et al, 2017). Studies investigating the relationship between vitamin D and depression are the most common.…”
Section: Introductionmentioning
confidence: 99%
“…We identified 12 SRs [31,100,156,[172][173][174][175][176][177][178][179][180] covering 31 original publications between 1998 and 2017, plus five SRs [181][182][183][184][185] on depression in women before and after childbirth (Supplemental Tables S18-S21 and Figure S5). Most studies relied on dimensional self-ratings of depressive symptoms as outcome measures.…”
Section: Resultsmentioning
confidence: 99%
“…Pregnancy, the postpartum period, and in particular the perinatal period are associated with an increased risk of depression in women. In five SRs of mainly high quality, results have been summarised covering largely overlapping subsets of 11 original studies between 2010 and 2017 [181][182][183][184][185]. One SR summarised observational cohort studies [184], two SRs summarised the results of secondary analyses of a RCT and cohort studies [181,183], and one SR summarised the results of a RCT, secondary analyses of two RCTs and cohort studies [182].…”
Section: Postpartum and Antepartum Depression (Primary Prevention)mentioning
confidence: 99%
See 1 more Smart Citation